GAYA KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU HONORER DI SMA NEGERI 1 ANJONGAN KABUPATEN MEMPAWAH - Rezeki, Yosi Astri; Sukmawati, Sukmawati; Chiar, M (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe purpose of this study was to determine the style of principals who gave punismen to honorary teachers, as well as transfer fees and barriers to principals in 1 Anjongan Public High School, Mempawah District. describe (1) the leadership style used by the principal in giving rewords to honorary teachers at SMA 1 Anjongan, Mempawah Regency; (2) the leadership style of the school principal in giving punismen to honorary teachers in SMA 1 Anjongan in Mempawah Regency; (3) the leadership style of principals in mobilizing honorary teachers at SMA 1 Anjongan in Mempawah Regency; (4) factors that hinder the leadership style of principals in SMA Negeri 1 Anjongan, Mempawah District. With a qualitative approach and a type of case study research, this thesis is structured using direct observation, direct communication (interviews), documentation techniques. Data analysis uses data collection, data reduction (data reduction), data presentation (data display) and verification and conclusion. The purpose of this study was to find out the style of the principal giving reword and punismen to honorary teachers, as well as moving honorariums and barriers to principals in 1 Public High School Anjongan, Mempawah Regency. Leadership continues to change according to the role being played, the ability to empower (subordinate) subordinates / members so that the initiative arises to be creative in work and the results are more meaningful for the organization with the leader once directing, moving, and influencing members.Keywords: Leadership Style, Punishment, Reward, Honorary Teacher